Valve interstitial cell culture: Production of mature type I collagen and precise detection - Liskova, Jana; Hadraba, Daniel; Filova, Elena; Konarik, Miroslav; Pirk, Jan; Jelen, Karel; Bacakova, Lucie (Microscopy research and technique, 2017)
Collagen often acts as an extracellular and intracellular marker for in vitro experiments, and its quality defines tissue constructs. To validate collagen detection techniques, cardiac valve interstitial cells were isolated from pigs and cultured under two different conditions; with and without ascorbic acid. The culture with ascorbic acid reached higher cell growth and collagen deposition, although the expression levels of collagen gene stayed similar to the culture without ascorbic acid. The fluorescent microscopy was positive for collagen fibers in both the cultures. Visualization of only extracellular collagen returned a higher correlation coefficient when comparing the immunolabeling and second harmonic generation microscopy images in the culture with ascorbic acid. Lastly, it was proved that the hydroxyproline strongly contributes to the second-order susceptibility tensor of collagen molecules, and therefore the second harmonic generation signal is impaired in the culture without ascorbic acid.
Keywords: Heart Valves; kolagen typu I; srdeční chlopně; Leydig Cells; collagen; porcine VIC; Collagen Type I; zvířata; Cells, Cultured; second harmonic generation; barvení a značení; cell culture; Swine; ascorbic acid; Male; fluorescent microscopy; kultivované buňky; Animals; Cell Culture Techniques; Leydigovy buňky; mužské pohlaví; Staining and Labeling; prasata; buněčné kultury